2018
DOI: 10.3390/fib6040081
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Density and Fiber Size on Porosity and Thermal Conductivity of Fiberboard Mats

Abstract: The thermal conductivity and porosity of fiberboard mats are crucial parameters for efficient energy consumption of the hot-pressing process and for final panel quality. In this work, the effect of fiber size and mat density on porosity and thermal conductivity of the mat were investigated. The fiber size was characterized as fine, medium and coarse. The mat porosity was measured by image analysis using the black and white contrast method. The thermal conductivity was determined at different density levels wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
(45 reference statements)
1
10
1
Order By: Relevance
“…In [31], the authors also reported a decrease in porosity percentage of particleboard, although the increase in adhesive content was higher. The porosity percentage was lower in comparison to that reported by [32]. Nevertheless, the technique used for porosity determination was different.…”
Section: Physical and Mechanical Propertiescontrasting
confidence: 73%
See 2 more Smart Citations
“…In [31], the authors also reported a decrease in porosity percentage of particleboard, although the increase in adhesive content was higher. The porosity percentage was lower in comparison to that reported by [32]. Nevertheless, the technique used for porosity determination was different.…”
Section: Physical and Mechanical Propertiescontrasting
confidence: 73%
“…The internal bond values meet requirements for roof insulation board (grade 1 and grade 2), wall sheathing regular and structural, and ceiling panels. (22) 672 (17) 113 (21) 1142 (10) Board-CG1:CA0.66-20% 338 (4) 1.10 25692 (10) 154 (25) 1062 (13) Board-CG1:CA1-14% 332 70.91 (29) 651 (18) 117 (18) 1206 (8) Board-CG1:CA1-20% 332 71.13 (23) 575 (32) 141 (30) 1030 (10) ASTM C208-12 1 160-497 0.97-2.76 345-1379 23.9-38.3 100-105…”
Section: Physical and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of fine fraction of the bark boards, the pores are smaller and closed. That is why the static and convection effect is minor compared to the coarse fraction boards at the same density [ 6 , 52 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important parameters influencing these factors is the size of the fibres. Many researchers have studied the effect of changing the size of natural fibre particles in the thermoplastic matrix like polyester, polylactic acid, polyvinyl chloride, polypropylene polyethylene and others [23][24][25][26][27][28][29][30][31]. They have obtained different results which sometimes lead to contradictory conclusions.…”
Section: Introductionmentioning
confidence: 99%